Educação das relações étnico-raciais e produção de textos na escola: traços, letras, cores e vozes das crianças - Bonifácio, Solange (2015)
This study is dedicated to understanding the development of school educational processes guided by the inter-relationship between education of ethnic-racial relationships and activities of reading and writing texts production, during proposals made in the course of an intervention carried out by the teacher-researcher. Teaching strategies, planned for intervention, were guided by the Ministry of Education Report 003/2004 and teaching and learning objectives related to reading and writing literacy in children, so it was developed with students from seven and eight years – 2nd year (1st series) – from a public school in the State of São Paulo. It is characterized as a qualitative research methodology inspired by phenomenology, which contributed to understanding the phenomenon of the interface of education of ethnic-racial relations and language development. It is based, theoretically, in the discussion on the approach of the ethnic racial relations of Silva (2009), problematizing the work of textual production from Possenti (2001; 2002; 2013), Tfouni (1988, 2011) and Assolini (2006), seeking to understand the representations (das Smolka, 2012) and the process of construction of the black identity (MUNANGA, 2003; Gomes, 2003) of children in the process of development of reading and writing in school. The data were recorded on video and field note registers, which after transcription and systematic analysis revealed the dimensions from three perspectives: teaching activities; children’s development; and collective interactions. The contribution of this research concerns the possibility of extending the possibilities to understand the contributions of education of ethnic-racial relationships to the acquisition of the written language in the context of school. It was possible to identify that, in the environment studied, the development of students identity was closely related to the development of important skills of reading and writing in positive and constructive interconnections.